Investment policy for non-maturity deposits in a corporate bank - Dolejš, Martin; Witzany, Jiří, 1966-; Derner, Tomáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The goal of this thesis is to propose an investment strategy for non-maturity corporate deposits in closely unspecified Bank in the Czech market. This topic falls in banks within the responsibilities of the asset liability management unit which is concerned mainly with the liquidity and interest rate risks of the banking book. According to theory the liquidity and interest rate risks may be reduced by aligning the assets to the structure of liabilities. The aggregated deposits portfolio is scrutinized through various analytical methods in order to capture the patterns of their behavior. The investment strategy is based on the output of the analysis which enables to match the asset structure to the liabilities and consequently reduce the liquidity and interest rate gaps. The investment strategy is elaborated based on the Sound Principles of Liquidity Management issued by the Bank for International Settlements in 2008.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses